Determinants of Anti‐Trafficking Policies: Evidence from a New Index1. (April 2014) - Cho, Seo‐Young; Dreher, Axel; Neumayer, Eric
Abstract We develop an index measuring the three main dimensions – prosecution, protection, and prevention – of the anti‐trafficking policies of the governments of up to 180 countries over the 2000−2010 period. Overall, developed countries perform better than the rest of the world; compliance with prosecution policy is highest, while governmental efforts to protect victims of human trafficking remain weakest. We employ the new indices to investigate which factors determine anti‐trafficking policies. We find that compliance with anti‐trafficking policies significantly decreases with corruption and is higher in countries that also respect the rights of women. We also find some tentative evidence for spatial dependence in anti‐trafficking policies.